An Inscribed Sherd in Aramaic Script from Barikot, Pakistan - Zellmann-Rohrer, Michael; Olivieri, Luca Maria 1962- (2019)
This article discusses a sherd inscribed with a text in Aramaic script from Barikot in Pakistan. The site, known in classical sources on Alexander the Great, has been regularly investigated over the last 40 years. In recent excavation campaigns, new evidence of the earliest phases of the city (500-50 b.c.e.) has been discovered, including the sherd treated here, among other inscribed pottery in Greek and Brāhmī.
Keywords: ARAMAIC texts; Aramaic script; Barikot; EXCAVATION; Inscriptions; POTSHERDS; Pottery; Pakistan; Inscription; sherd